FRI0237 Outcome of aortic involvement in giant cell arteritis (GCA) after 1-year follow-up: Prospective study using computed tompography angiography (CTA). (23rd January 2014) - Prieto-González, S.; Arguis, P.; García-Martínez, A.; Corbera-Bellalta, M.; Tavera-Bahillo, I.; Espígol-Frigolé, G.; Planas-Rigol, E.; Alba, M.A.; Hernández-Rodríguez, J.; Cid, M.C.
Abstract : Background: A prospective study of 40 patients with newly diagnosed, biopsy-proven GCA patients disclosed CTA signs of aortitis in 65% of patients 1 . The involvement by segments was as follows: ascending aorta 30%, aortic arch 57, 5%, descending thoracic aorta 57, 5%, and abdominal aorta 47, 5%. Moreover, 15% of patients already had aortic dilation at the time of diagnosis. Objectives: To prospectively evaluate the outcome of aortic involvement by comparing CTA findings at the time of diagnosis and those obtained after 1 year of treatment in the same patient cohort. Methods: The 40 patients evaluated at diagnosis were prospectively treated and followed by the investigators according to a defined protocol and were scheduled a new CTA examination after 1 year of treatment. Vessel wall thickness and vessel diameter at the aforementioned four aortic segments were evaluated. Aortitis was defined as circumferential aortic wall thickness ≥2 mm with or without contrast enhancement of the vessel wall observed in zones without adjacent atheroma. Results: Five out of the 40 patients were lost to follow-up or declined a new CTA, and in 10, CTA is still pending. Follow-up CTA has been completed in the remaining 25 patients. CTA findings of aortitis were still present in 10 (62, 5% of the patients who initially had aortitis). Nevertheless, significant reduction in mean wall thickening was detected in all but one of the aortic segments: ascending aorta (1, 5±0, 8 vs 1, 2±0, 6 mm, p=0, 13), aortic arch (2, 3±1, 0 vs 1, 7±0, 8 mm; p=0, 02), descending thoracic aorta (2, 8±1, 1 vs 2, 1±1, 0 mm; p=0, 02), and abdominal aorta (1, 7±0, 8 vs 1, 2±0, 6 mm; p=0, 02). None of the 25 patients evaluated developed new lesions in previously unaffected areas. Similarly, no patients lacking aortitis in the first CTA developed new aortic involvement. Similar to the first evaluation, aortic arch and descending thoracic aorta were the most affected segments (32% each), and abdominal aorta and ascending aorta were involved in 20 and 12% of patients, respectively. Interestingly, aortic diameters remained stable. No patients developed new aortic dilation or increase in previous dilations. Conclusions: After 1 year of glucocorticoid treatment, CTA signs of aortitis persisted in 62.5.% of the patients who presented initial aortic inflammation. However, aortic thickening significantly decreased and there were no changes in aortic diameters during this period of time. Longer follow-up is necessary to determine clinical significance of these inflammatory findings and their possible relationship with dilation. Supported by SAF 08/0438 and SAF 11/30073. References: Prieto-González S, et al. Large vessel involvement in biopsy-proven giant cell arteritis: prospective study in 40 newly diagnosed patients using CT angiography. Ann Rheum Dis. 2012 Jan 20 [Epub ahead of print] Disclosure of Interest: None Declared